The Effect of Ease of Payment and User Experience on User Retention through Monetization Models in Digital Games - Jonathan Halomoan Simanjuntak; Afidah Nur Aslamah; Osly Usman; Ryna Parlyna (Asosiasi Transformasi Digital Dan Bisnis Indonesia, 2025)
This study aims to analyze the influence of Ease of Payment (X1) and User Experience (X2) on User Retention (Z), mediated by Monetization Models (Y), addressing empirical inconsistencies in the literature regarding post-adoption behavior in digital games. Utilizing a quantitative explanatory design, data were collected from 158 students at the Faculty of Economics and Business, Universitas Negeri Jakarta, who are active microtransaction users. The hypothesis was tested using Partial Least Squares-Structural Equation Modeling (PLS-SEM). The results confirmed that both X1 and X2 significantly and positively influence Y and that X2 is the strongest direct predictor of Z (β = 0.723). Critically, the hypotheses related to the mediating role of Y (H6) and (H7) and the direct effect Y → Z (H3) were rejected. This outcome supports the study's main contribution: the postulation of Functional Isolation, which concludes that financial commitment (Monetization) is an independent utility transaction that does not reinforce psychological commitment (Retention). The primary implication is that for sustainable long-term engagement, developers must strategically prioritize investment in core User Experience (X2) rather than relying on the Monetization Model to secure user loyalty.